PENERAPAN REGULASI BANK TERKAIT PENILAIAN RGEC DAN DAMPAKNYA PADA NILAI PERUSAHAAN PERBANKAN - Wulandari, Dewa Ayu Eny; Mertha, Made (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
The regulation about the health of bank which used Risk profile, Governance, Earning, Capital (RGEC) must be applied by banks in 2011.The result from assessment of RGEC could impact in preseption of investors about performance of bank. The purpose of this research was to analyze the effect of implementation from the health assessment of bank using RGEC on the firm value. The banks were listed in BEI is used to this research in period 2013-2015. This research had sixty banks as samples with used purposive sampling technique. Risk profile and GCG measured by composit value of selfassement, meanwhile earning measured by ROA and capital measured by CAR. Firm value used tobin’s q as measurement. The result showed that risk profile partially influence negative to the firm value. GCG and earning partially influence positive to the firm value Meanwhile variable of capital not influence to the firm value of bank.
Keywords: Risk profile, GCG, Capital, Firm Value of Bank